0=
=0
x-=0
x*(1-x)=0
x=0 1-x=0
x=0 x=1
0 1
x1=0 x2=1
1.b3=b1*q^2,
b5=b1*q^4
b6=b1*q^5
2.4=b1*q^2
0.32=b1*q^4 разделим 2-ое уравнение на первое, получим
q^2=0,32/2,4
q^2=0.02*2^4/0.3*2^3
q^2=0.02*2=0.3=4/30=2/15
q=√2/15=0.36
b6=b5*q^5=0,32*(0.36)^5=0.32*0.006=0.00192
2.b1=18,b2=-12,b3=8
q=b2/b1=-12/18=-2/3
Sn=b1(q^n-1)/(q-1)=18*(-2/3)^n-1)/-2/3-1=18*( (-2/3)^n-1)/-5/3=54/5*(-2/3)^n-1)
3.x1=0.48, x2=0.32
q=x2/x1=0.32/0.48=2/3
S10=x1(q^10-1)/q-1=0.48(2/3)^10-1)/2/3-1=0.48(1024/59049-1)/-1/3=0.48*58025/59049/-1/3=27852/59049*(-3)=-83556/59049=-1.42
4.0.2(3)=23/100
Объяснение:
x-x²≥0
-x²+x≥0
x²-x≤0
нули
x²-x=0
x(x-1)=0
x=0
x-1=0
x=1
x∈ [ 0 ; 1 ]